Improved pulse shaping for PAPR reduction of OFDM signal - Zhuo-ming FENG; Wei-zhong LIU; Xiong-fei TAO; Bai-yun LUO (Tongxin xuebao)
An improved Nyquist pulse was presented.The proposed pulse waveform can significantly reduce the PAPR and keep the system BER invariant at the same time,but at the expense of a little spectrum loss.Simulation results show that the proposed shaping pulse can get better performance of PAPR compared to traditional raised cosine pulse and flipped-exponential pulse.It is an effective method with low complexity to reduced the PAPR of OFDM signal by pulse shapping with the proposed nyquist pulse.